WinDix Training Manual for Standardized Patients: How to Give Effective Feedback - Dixie Fisher (Association of American Medical Colleges, 2006)
Abstract Introduction This manual is a concise seven-step approach for helping standardized patients (SPs) learn to give effective feedback to students. Methods The manual includes objectives, quizzes, and a Quality of Standardized Patient Feedback evaluation instrument. Although this manual is meant to accompany a trainer's manual, SPs may find the information helpful even without a formal face-to-face training session. Results We found that the manual, when used for SP training, greatly improves the quality of the feedback that SPs give to students. Anecdotal reports from SPs revealed that they have greater confidence in giving feedback to students. A review of the video tapes of the cases revealed that the SPs' feedback was more specific. Students stated that the feedback they received from SPs was specific enough to make behavioral changes. Student evaluations expressed greater satisfaction when SPs were trained using this manual than without the training. Discussion The training manual effectively trains SPs to give more detailed feedback to students in a way that can translate to a behavioral change.